Realizing the sustainable potential of Indonesian marine tourism through effective and participatory local tourism governance - Asdar, Yuliana; Abdullah, Muh Tang (Edelweiss Applied Science and Technology, 2024)
Mandala Ria Beach in Bulukumba Regency, South Sulawesi, possesses significant marine tourism potential but faces various challenges in its development. This study aims to analyze the application of Local Tourism Governance principles and their impact on community welfare and destination sustainability. Employing a qualitative approach that combines literature review, field observations, and in-depth interviews. The collected data was analyzed qualitatively using NVivo 12 Plus software to identify patterns and themes. The findings reveal that collaboration among village government, local communities, and the Bulukumba Regency Tourism Office is key to overcoming constraints such as limited infrastructure, weak human resource quality in tourism, and environmental conservation issues. Local Tourism Governance at Mandala Ria Beach encompasses aspects of transparency, accountability, vision and leadership, acceptance of diversity, knowledge and skill development, and clarity of roles and responsibilities of all stakeholders. However, the absence of an official Memorandum of Understanding (MoU) between the Tourism Office and the Ara Village Government, as well as potential land ownership conflicts, pose challenges in optimizing sustainable tourism development. This study recommends the formulation of more integrated and community-oriented tourism strategies and policies, involving dialogue and coordination among stakeholders, and the development of guidelines for destination management, human resource capacity building, and preservation of local environment and culture. Consequently, the development of Mandala Ria Beach tourism is expected to provide equitable and sustainable benefits for all parties involved.